PERAN GURU DALAM MENINGKATKAN DISIPLIN BELAJAR SISWA STUDI KASUS DI SD INPRES ANTANG II - Ahmad Jais Banyal; R Supardi; Muh. Khaedar; Syamsul Alam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the role of teachers in improving student learning discipline in SD Inpres Antang II. The focus of the study includes the role of teachers, strategies to improve discipline, and forms of student indiscipline. The method used is a qualitative approach through observation and interviews. Subjects consisted of three homeroom teachers (grades 4, 5, and 6) and five students from each class. The results showed that teachers play an important role in shaping student discipline, not only as teachers, but also as mentors and character builders. Teachers are required to be patient, understand students ‘ backgrounds, and use an empathic approach and open communication. Strategies implemented include understanding the emotional state of students and the creation of a safe and supportive learning atmosphere. Forms of indiscipline found include: not paying attention to lessons, chatting while studying, not doing assignments, forgetting to bring equipment, and arriving late. This study confirms the importance of the role of teachers in building discipline as part of student character education.